Adhesives for adhering polystyrene plastic and their long-term effect. (March 2015) - Winther, Thea; Bannerman, Judith; Skogstad, Hilde; Johansson, Mats K. G.; Jacobson, Karin; Samuelsson, Johan
Abstract : To guide conservators in their decisions in active conservation of polystyrene materials, seven adhesives were tested before and after light ageing. The material was investigated by assessment of working properties, appearance, colour measurement, tensile testing, hardness measurement, assessment of break type, scanning electron microscope imaging, and assessment of reversibility. Based on a survey among conservators, the adhesives included were acrylates (Paraloid ® B-72 in acetone: ethanol, or only ethanol, Paraloid ® B-67 in isopropanol, Primal ® AC 35, Acrifix ® 116), epoxies (HXTAL ® -NYL-1, Araldite ® 2020) and one cyanoacrylate (Loctite ® Super Attack Precision). Adhesives were tested on extruded sheets of transparent, general purpose polystyrene applied on joined edges and as an open layer. Damage to the plastic could be seen for Acrifix ® 116 and Loctite ® Super Attack Precision. The average break force sensitivity values indicate that the cyanoacrylate was weakened while Acrifix ® 116 was strengthened after ageing. In general, the cyanoacrylate was the strongest and Paraloid ® B-67 the weakest. Most adhesives showed yellowing after ageing apart from Acrifix ® 116 and HXTAL ® -NYL-1. The Paraloids, Primal ® AC 35, and the epoxies were possible to remove from the plastic.